Market segments for groundnuts: Recent insights from Tanzania - Rutsaert, Peter (CGIAR, 2023)
Tanzania is the second largest producer of groundnuts in East Africa, following Sudan, with an annual production of roughly 700 000 MT. Teams from Market Intelligence, Accelerated Breeding and Tanzania Agricultural Research Institute (TARI) are working with the Tanzania Groundnut Product Design Team (PDT)—a team whose members represent the groundnut value chain, from farmers and processors to seed producers—to discuss the knowns and unknowns of requirements for groundnut production and processing. The PDTs are established by the Accelerated Breeding Initiative (ABI) TRANSFORM per crop per country to ensure feedback of relevant stakeholders on the market segments and target product profiles.